Spatial Analysis of Regional Development : A Block Wise Study, Faizabad District - Sadaf; Munir, Abdul (National Geographical Journal of India, 2022)
Regional development is a multi-dimensional phenomenon. It represents an overall development of any region. The concept of regional development means the fullest development of any region according to its potentialities. The problem of regional disparities is not found in India only rather it is a global problem. However, in India, it is more common than in any other country. The present paper is an attempt to show the spatial pattern of regional development at block level of Faizabad district for the period of 2010-2011. Twenty two variables have been selected for analyzing the spatial variation of development of 11 blocks of the district. For this study, secondary data have been collected from the stastical bulletin and primary census abstract. Composite index of development and Z score have been used to calculate the agricultural development, infrastructural development, industrial development, socio-economic development and finally the level of overall development. The analysis revealed that Amaniganj holds the first position while Rudauli attains the low level of development.